Histopathological changes in internal organs of white rats after exposure to curare-like drugs - Mishalov , V.D.; Maievskyi , O.Ye.; Kozlov, S.V.; Moskalenko , V.S. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. The relevance of the topic of diagnosing fatal poisoning with muscle relaxants in forensic medicine has emerged relatively recently and is due to an increase in the frequency of such cases in forensic medical practice. Analysis of the literature has shown that Suxamethonium chloride is most often used as a means of causing unlawful actions. Objective. Taking this into account, we set the goal of our study to determine the characteristic histopathological changes in internal organs of white rats after exposure to succinylcholine chloride in experimental conditions. Methods. To achieve the goal of the study, we conducted an experimental study on 32 sexually mature rats. All animals were randomly divided into three groups: group 1 consisted of intact rats (n=6), group 2 consisted of control rats (n=6), and group 3 consisted of experimental animals (n=20) (intramuscular injection of 0.5 ml of an aqueous solution of Suxamethonium chloride). After euthanasia, the rats’ brains, lungs, hearts, livers, and kidneys were removed by postmortem autopsy for further pathohistological examination. Results. Histopathological analysis of acute blood supply disorders with multiple small-focal hemorrhages, pulmonary and cerebral edema detected in the internal organs of experimental animals pulmonary and cerebral edema after intramuscular administration of 0.5 ml of an aqueous solution of Suxamethonium chloride indicates sudden asphyxial death. Acute circulatory disorders with pericell and paravasal edema may also indicate the toxic effects of suxamethonium chloride. Conclusion. The problem of diagnosing fatal poisoning with muscle relaxants can be solved using modern morphological research methods. The changes in the internal organs of experimental animals obtained as a result of histopathological analysis indicate the acute toxic-hypoxic effect of Suxamethonium chloride, but cannot be considered specific to this drug alone. The histopathological picture revealed during autopsy in cases of unknown circumstances of death is the basis for further thorough toxicological analysis of the fluids and tissues of the deceased in order to establish the damaging chemical factor.